Structural Changes of Myofibrillar Proteins in Marinated Duck Drumsticks during Ultra-high Pressure Processing Treatment - Jingjiu LI; Mingfei SONG; Yue NIU; Lingjiao ZHU; Danjun GUO; Wei XU; Yang YI; Hongxun WANG (Shipin gongye ke-ji)
To investigate the improvement mechanism of ultra-high pressure treatment on the tenderness of marinated duck drumsticks, this study analyzed the pattern of structural changes of myofibrillar proteins during ultra-high pressure processing (400 MPa, 15 min) by determining the surface hydrophobicity, sulfhydryl content, chemical force, secondary structure and microstructure. The results showed that the hydrophobicity of myofibrillar proteins initially increased and then decreased, reaching a maximum of 51.03 after 12 min of treatment. The total thiol content decreased by 40.6% after 15 min of treatment, while the free thiol content increased by 42.7%, and disulfide bonds significantly (P<0.05) increased by 189.2%. Tryptophan and tyrosine residues were exposed, indicating changes in protein tertiary structure. After 15 min of ultra-high pressure treatment, the α-helix content of myofibrillar protein decreased from 20.63% to 13.45%, and the content of irregular coils increased from 23.93% to 28.67%, suggesting rearrangement of the protein secondary structure. SDS-PAGE electrophoresis and scanning electron microscopy results demonstrated protein depolymerization of ultra-high pressure processing treatment, significant reduction in particle size, and more uniform distribution. In conclusion, during ultra-high pressure processing, significant changes occur in the tertiary structure, secondary structure, and microstructure of duck drumsticks myofibrillar proteins, contributing to the improvement of duck meat tenderness. This study would provide a theoretical basis for the application of ultra-high pressure technology in improving meat tenderness.